2013
DOI: 10.1002/eji.201243007
|View full text |Cite
|
Sign up to set email alerts
|

Both the nature of KIR3DL1 alleles and the KIR3DL1/S1 allele combination affect the KIR3DL1 NK‐cell repertoire in the French population

Abstract: NK-cell functions are regulated by many activating and inhibitory receptors including KIR3DL1. Extensive allelic polymorphism and variability in expression can directly alter NK-cell phenotype and functions. Here we investigated the KIR3DL1+ NK-cell repertoire, taking into account the allelic KIR3DL1/S1 polymorphism, KIR3DL1 phenotype, and function. All 109 studied individuals possessed at least one KIR3DL1 allele, with weak KIR3DL1*054, or null alleles being frequently present. In KIR3DL1 high/null individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 56 publications
(79 reference statements)
2
25
0
5
Order By: Relevance
“…Thus, the formation of the KIR2D NK repertoire is probably finely adjusted depending on the KIR2DL polymorphism and on the other NK cell subsets. In this regard, we have recently shown the impact of KIR3DL1 allelic nature on KIR3DL1 NK repertoire formation (37). These recent investigations suggest primary expression of KIR3DL1 followed by KIR2D acquisition.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, the formation of the KIR2D NK repertoire is probably finely adjusted depending on the KIR2DL polymorphism and on the other NK cell subsets. In this regard, we have recently shown the impact of KIR3DL1 allelic nature on KIR3DL1 NK repertoire formation (37). These recent investigations suggest primary expression of KIR3DL1 followed by KIR2D acquisition.…”
Section: Discussionmentioning
confidence: 80%
“…Emerging data suggest that two polymorphisms within the KIR3DL1*004 allele (Leu 86 and Ser 182 ) negatively affect protein folding, resulting in significantly reduced cell surface expression (18,61,(65)(66)(67). NK cells dimly expressing the KIR3DL1*004 (71,72). Simple dichotomies in NK cell receptor-ligand binding affinities and definitions of cognate KIR-ligand interactions have also been questioned and further limit our ability to predict in vivo NK cell function (20,73).…”
Section: Discussionmentioning
confidence: 99%
“…9 For some dUCBT, KIR genotyping with an INVITROGEN kit was performed to allow the assessment of KIR2DL5 alleles and KIR3DL1 alleles were assigned as already reported. 8 KIR genes involved in the evaluation of chimerism status are highlighted in black boxes. Results indicate full donor chimerism from UCB 1.…”
Section: Letters To the Editormentioning
confidence: 99%
“…Natural killer (NK) cells are the first population to reconstitute the patient's hematopoietic system following hematopoietic stem cell transplantation, before T lymphocytes, 7 and we previously reported that cord blood NK cells express killer cell immunoglobulin-like receptors (KIR). 8 Here, we investigated KIR genes as additional markers for early chimerism assessment after dUCBT. KIR gene content varies between individuals who can exhibit seven to fourteen inhibitory and activating KIR genes, defining multiple KIR genotypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation